DNA-Based Genetic Markers for Rapid Cycling Brassica Rapa (Fast Plants Type) Designed for the Teaching Laboratory - Slankster, Eryn E.; Chase, Jillian M.; Jones, Lauren A.; Wendell, Douglas L. (Frontiers in Plant Science, 2012)
We have developed DNA-based genetic markers for rapid-cycling Brassica rapa (RCBr), also known as Fast Plants. Although markers for Brassica rapa already exist, ours were intentionally designed for use in a teaching laboratory environment. The qualities we selected for were robust amplification in PCR, polymorphism in RCBr strains, and alleles that can be easily resolved in simple agarose slab gels. We have developed two single nucleotide polymorphism (SNP) based markers and 14 variable number tandem repeat (VNTR)-type markers spread over four chromosomes. The DNA sequences of these markers represent variation in a wide range of genomic features. Among the VNTR-type markers, there are examples of variation in a nongenic region, variation within an intron, and variation in the coding sequence of a gene. Among the SNP-based markers there are examples of polymorphism in intronic DNA and synonymous substitution in a coding sequence. Thus these markers can serve laboratory exercises in both transmission genetics and molecular biology.